Influência do intervalo entre a inseminação artificial com sêmen diluído resfriado e transportado e a ovulação sobre a fertilidade de éguas - Silva, J. M.; Valle, G. R.; Saturnino, H. M.; Palhares, M. S.; Oliveira, H. N. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1998)
One hundred forty seven cycles of mares were allocated in a completely randomized experiment, with different number of replications and divided in four treatments (T1 = 24 hours preovulation; T2 = 48 hours preovulation; T3 = 48 hours preovulation and in tbe same day of ovulation; T4 = 72 hours preovulation and in the same day of ovulation), in order to study the effect of AI/ovulation interval on mare fertility. The mares were inseminated three times for wek (monday, wednesday and friday), with semen of only one stallion diluted in extender skim milk-glucose, using a volume of 15ml, with 400 x 10(6) sptz viable, cooled at 14 degrees C/3.6 hours, and transported in modified container Celle. Conception rates were not different according to the treatments. So, observed spermatic survival for 60 hours showed the practicability of the inseminations on monday, wednesday and friday.
Effects of AI-ovulation intervals on fertility of inseminated mares with diluted, cooling and transported semen
Keywords: equine; insemination/ovulation interval; conception rate